Differences in aggression in Polish men and women in different age groups - Rytel, Jolanta (Studia Psychologica: Theoria et praxis, 2011)
This paper aims at exploring differences in levels of aggression of men and women in different age groups (10 to 79 years). Additionally, it provides information on psychometrie characteristics of Buss-Perry Aggression Questionnaire (Amity version) by age. Sexual selection theory proposes that sex difference in physical aggression are due to greater male than female competition for reproduction which leads males to use more risky strategies. In line with the theory, the largest divergence between men’s and womens physical aggression was observed in the age group 16-22. The differences were smaller in both younger and older age groups. The results seem to support the theory of sexual selection, but their validity should be further confirmed on larger samples, in particular, with a bigger share of older individuals (above 55 years old).